PRELIMINARY PHYTOCHEMICAL SCREENING OF BIOACTIVE CHEMICALS IN SUNFLOWER (Tithonia diversifolia) ROOTS - Ahmed, S.O; Bamigboye Samson. O (International Journal of Human Computing Studies, 2020)
Plants are the most available sources of nutrients and phytochemicals; they have also played an important role in the development of drugs and treatment of various ailments in many countries. Therefore, this study was carried out to ascertain the preliminary phytochemical screening of bioactive chemicals in wild sunflower (Tithonia diversifolia) root. The solvents used for extraction includes: petroleum ether, methanol and distilled water. Results revealed that tannins, flavonoids, phenols, steroids, glycosides, carbohydrates and protein were present in the aqueous extract; only saponins were not detected in the sample. Methanol and petroleum ether follow similar pattern as tannins, flavonoids, phenols, steroids, glycosides, saponins carbohydrates and protein were all present in the sample. It was concluded that the extract contained several bioactive chemicals which could confer it the ability to have therapeutic or pharmacological effects on human and animals.